Cross-border Movement of People between Russia and Poland and Their Influence on the Economy of Border Regions - Zaitseva, Natalia A.; Korneevets, Valentin S.; Kropinova, Elena G.; Kuznetsova, Tatyana Yu.; Semenova, Ludmila V. (International Journal of Economics and Financial Issues, 2016)
The ever-increasing role of cross-border movement for the development of the economies of the regions of neighboring countries located in the immediate vicinity of the border defines the topicality of this research. It is important to continually assess the dynamics of cross-border cooperation, reflecting the change in the foreign policy interaction between the Russian Federation and neighboring countries in Europe, to develop timely measures to minimize the negative consequences of such tendencies. The aim of research was to analyze the dynamics of cross-border movements and exchanges between the residents of the Kaliningrad Region and Poland, the assessment of the objectives' structure of visits and the distance from the border to the visit target. As a result of the research was compiled a “portrait” of the main groups of residents of the Kaliningrad region and Poland participating in cross-border movements, and authors' assessment of the positive and negative effects of such movements and exchanges on the economic development of these regions is given. Keywords: trans-border cooperation, regional development, economic cooperation, tourism, Kaliningrad region, Russia, Poland JEL Classifications: F63, R11